Trends Analysis of Non-Hodgkin Lymphoma at the National, Regional, and Global Level, 1990–2019: Results From the Global Burden of Disease Study 2019 - Cai, Wenwen; Zeng, Qingle; Zhang, Xingxing; Ruan, Weiqing (Frontiers in Medicine, 2021)
Background: Non-Hodgkin lymphoma (NHL) is a common hematologic malignancy. This article aimed to estimate the trends of non-Hodgkin lymphoma (NHL) globally from 1990 to 2019. Methods: Data on NHL burden were explored from the Global Burden of Disease study 2019. The trends of NHL burden were estimated using age-standardized rate (ASR) and estimated annual percentage change (EAPC). Results: The ASR of NHL incidence showed an increasing trend worldwide from 1990 to 2019, with the EAPC of 0.56 (95% confidence interval [CI]: 0.45 to 0.66). Meanwhile, increasing trends were observed in both sexes, most geographic regions, particularly East Asia (EAPC = 3.57, 95%CI: 3.29 to 3.86). The most pronounced increasing trends were seen in Georgia (EAPC = 4.70, 95%CI: 4.20 to 5.21), followed by Belarus and Uzbekistan. However, death and disability-adjusted life years (DALYs) caused by NHL showed decreasing trends globally, in which the respective EAPCs were −0.09 (95%CI: −0.17 to −0.02) and −0.28 (95%CI: −0.35 to −0.22). Decreasing trends mainly were seen in high and high-middle sociodemographic index (SDI) areas. At the national level, the largest increasing trends of death and DALYs were observed in Georgia, in which the respective EAPCs were 4.54 (95%CI: 4.01 to 5.07) and 4.97 (95%CI: 4.42 to 5.52). Conclusions: Decreasing trends of death and DALYs caused by NHL were observed worldwide from 1990 to 2019, but NHL remains a substantial challenge globally. The findings would inform the strategies for reducing the burden of NHL.